Moggerhanger a novel - Sillitoe, Alan 1928-2010 (Seven Stories Press, 2016)
"Moggerhanger by iconic British writer Alan Sillitoe is the third part in a trilogy and the first to be published here in America. Following from A Start in Life, and Life Goes On, it features Michael Cullen, who is now an aimless 40-year-old, a picaresque hero who always seems to end up in trouble. Having just left his job in advertising, he is employed by his old boss and gang-leader, Moggerhanger. From Nottingham, to London, to France and back, Cullen embarks on a series of journeys (most of them in a Rolls Royce) doing "jobs" for Moggerhanger while meeting a cast of strange and wonderful characters on the way...ranging from Labrador dogs, crazed poets and endless women, to the members of the Green-Toe-Gang, rat catchers, brothel workers, and investigative journalists. Whilst on his adventures he is joined by his old friend and ex-mercenary soldier, Sergeant William Straw, and is constantly overlooked and entertained by his outrageous father, the famous writer Blaskin, and Blaskin's long-suffering girlfriend. A brilliantly funny and irreverent picaresque novel, Moggerhanger will, by turns, make you laugh, reel, sigh, and think again about the way we live our lives"...
Keywords: Picaresque literature; Humorous fiction; Satire; FICTION / Literary; HISTORY / Europe / Great Britain; FICTION / Satire; Middle-aged men -- Fiction; Interpersonal relations -- Fiction; Europa; Großbritannien